Observations concerning pigment production in a species of Serratia and effect of storage conditions on its pigmented and non-pigmented variants - Tiempo, Felina (Algarme) 1943- (1973)
This paper determined the effects of the presence or absence of certain nutrients such as peptones, beef extract and yeast extract on pigment production of Serratia species and the responses shown by its pigmented and non-pigmented variants on prolonged exposure to low temperature and dessication of medium.